2020
DOI: 10.1002/lno.11466
|View full text |Cite
|
Sign up to set email alerts
|

Coupled changes in traits and biomasses cascading through a tritrophic plankton food web

Abstract: Trait-based approaches have broadened our understanding of how the composition of ecological communities responds to environmental drivers. This research has mainly focussed on abiotic factors and competition determining the community trait distribution, while effects of trophic interactions on trait dynamics, if considered at all, have been studied for two trophic levels at maximum. However, natural food webs are typically at least tritrophic. This enables indirect interactions of traits and biomasses among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…In this study, we want to advance our understanding of how functional diversity affects ecosystem functioning in model communities by including a diverse third trophic level. Although it has often been highlighted how important the effects of the third trophic level on ecosystem functions are (Bruno and O'Connor 2005, Duffy et al 2007, Abdala‐Roberts et al 2019, Daam et al 2019, Ehrlich and Gaedke 2020), relatively few studies have attempted to take these effects into account explicitly. Ceulemans et al (2019) showed that functional diversity increases the biomass production, temporal stability, and biomass transfer efficiency to higher trophic levels of a tritrophic food web, when diversity is increased simultaneously at all three trophic levels.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we want to advance our understanding of how functional diversity affects ecosystem functioning in model communities by including a diverse third trophic level. Although it has often been highlighted how important the effects of the third trophic level on ecosystem functions are (Bruno and O'Connor 2005, Duffy et al 2007, Abdala‐Roberts et al 2019, Daam et al 2019, Ehrlich and Gaedke 2020), relatively few studies have attempted to take these effects into account explicitly. Ceulemans et al (2019) showed that functional diversity increases the biomass production, temporal stability, and biomass transfer efficiency to higher trophic levels of a tritrophic food web, when diversity is increased simultaneously at all three trophic levels.…”
Section: Introductionmentioning
confidence: 99%
“…The different feeding strategies such as passive (filter) or active (ambush) feeding can also be included to better characterize the trophic interaction (Wirtz 2012). The ingested prey is then converted to zooplankton biomass with a certain biomass conversion efficiency which can be different for different prey but often assumed the same (Ehrlich and Gaedke 2020).…”
Section: Predator-prey Interactionmentioning
confidence: 99%
“…As with most predator–prey interactions, the interaction between a phytoplankter and a zooplankter includes several processes, including prey encounter, selection, capture, ingestion and digestion (Flynn and Mitra 2016) and each of these processes are influenced by the interacting traits of both predator and prey. There are numerous modeling studies describing phytoplankton–zooplankton interactions that range in their generality and complexity (Banas 2011; Ehrlich and Gaedke 2020; Serra‐Pompei et al 2020). We provide a very brief overview here but the detailed descriptions of the different models can be found elsewhere (Tirok and Gaedke 2010; Serra‐Pompei et al 2020).…”
Section: Traits In Models Of Predator–prey and Host–virus Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we want to advance our understanding of how functional diversity affects ecosystem functioning in model communities by including a diverse third trophic level. While it has often been highlighted how important the effects of the third trophic level on ecosystem functions are (Bruno and O’Connor, 2005; Duffy et al, 2007; Daam et al, 2019; Abdala-Roberts et al, 2019; Ehrlich and Gaedke, 2020), relatively few studies have attempted to explicitly take these effects into account. Ceulemans et al (2019) showed that functional diversity increases the biomass production, temporal stability, and biomass transfer efficiency to higher trophic levels of a tritrophic food web, when diversity is increased simultaneously at all three trophic levels.…”
Section: Introductionmentioning
confidence: 99%